PROGRAM ADVOKASI PENDIDIKAN SEBAGAI UPAYA PENINGKATAN EFEKTIVITAS BELAJAR MENGAJAR DI SDN GUNUNGKUNING - Mubiin, Ajmal Nazirul; Enjang Rohiman; Sri Nurhasanah; Amelia Putri; Darmana Aries Setiawan (Makkareso: Riset Pengabdian Masyarakat, 2025)
Education plays a vital role in shaping students character, skills, and mindset. However, primary schools often face challenges due to monotonous, teacher-centered methods that reduce motivation and participation. This article presents the Educational Advocacy Program implemented through the Community Service Program (KKN “ORDA MITRA PEMDA”) of Sunan Gunung Djati State Islamic University Bandung, conducted in Gunungkuning Village, Majalengka, from July 20 to August 25, 2025. Using the SISDAMAS model with four cycles socialization, social mapping, participatory planning, and program implementation with evaluation the program involved 4th to 6th grade students at SDN Gunungkuning. Activities included demonstrations, ice breaking, interactive discussions, simple experiments, and bullying advocacy. The results show improved student enthusiasm, active engagement, and better understanding of lessons through interactive and digital-based learning. Teachers also enhanced their ability to design varied, engaging lessons and manage classrooms effectively. In addition, bullying advocacy raised awareness of building a safe and respectful school environment. The program demonstrates that educational advocacy can serve as an effective and innovative model for improving teaching and learning quality in rural primary schools.